2017
DOI: 10.1080/10438599.2017.1338392
|View full text |Cite
|
Sign up to set email alerts
|

Specialisation in key enabling technologies and regional growth in Europe

Abstract: This paper explores the specialisation of European Union (EU) regions in key enabling technologies (KETs) and assesses whether or not being specialised in these technological areas has an effect on regional growth. The evidence presented shows that regions specialised in KETs are concentrated in central Europe; however, over the period taken into account (1996â\u80\u932011), less innovative and peripheral EU regions have been increasing their specialisation in these technological areas at the expense of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
3
25
0
7
Order By: Relevance
“…The study in this paper finds that the results of the two externalities show differences when measuring economic efficiency with different indicators ( Table 7). Table 7, MAR externality exists in labor productivity and land productivity, which is consistent with the findings of some scholars [45,46,[49][50][51][52]. Jacobs externality exists in total factor productivity, which is consistent with the findings of some scholars [44,45,47,48].…”
Section: Specialization and Diversitysupporting
confidence: 86%
See 1 more Smart Citation
“…The study in this paper finds that the results of the two externalities show differences when measuring economic efficiency with different indicators ( Table 7). Table 7, MAR externality exists in labor productivity and land productivity, which is consistent with the findings of some scholars [45,46,[49][50][51][52]. Jacobs externality exists in total factor productivity, which is consistent with the findings of some scholars [44,45,47,48].…”
Section: Specialization and Diversitysupporting
confidence: 86%
“…Evangelista et al explored the specialization of key technologies in the European Union region and its impact on regional development. The econometric estimates in the paper indicate that specialization in key technologies will affect the region economic growth, and this effect is stronger in the EU region where innovation is weak [52]. Empirical research generally finds positive productivity gains from urban agglomeration, but estimates vary greatly in magnitude.…”
Section: Literature Reviewmentioning
confidence: 79%
“…What are the mechanisms that link innovation and growth in the current economic situation? Over the last years, we have heard, at least, three different views about the role that technological change could play to foster future economic development (for a critical appraisal of the Schumpeterian legacy on development, see Evangelista, 2018). Let see these views in turn.…”
Section: Is the Engine Of Creative Destruction Grinding To A Halt?mentioning
confidence: 99%
“…Applied macro models support the role of investment in R&D and intangibles, other than human capital, as necessary conditions to maintain long-term economic growth in Europe (Veugelers 2016). Recent evidence shows that investment in hi-tech has boosted economic growth (Evangelista et al 2018) and jobs creation in European regions (Goos et al 2018). Historical accounts of the role of publicly-funded research have shown that this type of policy brings about major technological change both directly and indirectly.…”
Section: Filling the Investment Gap In Europementioning
confidence: 99%
“…В-третьих, вкупе с последним активное развитие банковской сферы, крупных экономических проектов формирует инвестиционную активность. В-четвертых, снижение безработицы сглаживает остроту проблем, важных для государства в экономическом, социальном и политическом плане, ставящих под угрозу и национальную безопасность (бедность населения, семейные и прочие социальные конфликты, уровень преступности, число суицидов и в целом роста смертности в сочетании со снижением рождаемости, недоверие к власти на фоне снижения налоговых поступлений в бюджет и расходов из него на пособия по безработице, закрытие предприятий) [13][14][15].…”
Section: Introductionunclassified